(untitled) (Journal of Science and Technology, 2016)
This study investigates and explores avenue for effectively managing and increasing the availability of Graduate Students’ scholarship by submitting Theses and Dissertations in electronic format for easy accessibility and storage. This pilot study was done in the year 2009 with Graduate Students in the Faculties of Fine and Industrial Art in the Kwame Nkrumah University of Science and Technology (KNUST). Qualitative research was employed to appraise and analyse Theses and Dissertations (TDs) management in the School of Graduate Studies (SGS) and the University Library. In addition, graduate students’ knowledge of online publishing and the capabilities of the Network Operations Centre (NOC) of the KNUST in managing the Electronic Theses and Dissertations (ETDs) were reviewed. An online framework resource was designed and developed to manage and promulgate graduate research output in the structure of ETDs. This framework named “KNUSTVester” is founded on the philosophy of Open Access (OA) Initiative and mimicked the submission processes of the SGS and employed the Dublin Core Metadata Element Set (DCMES) for accessing the ETDs online. Testing of the online framework resource was done and the results confirmed that the submission of theses and dissertations electronically could be an effective tool for the promulgation of knowledge and skills in this 21st Century.